Can laptops be left inside passenger bags if motion imaging is used in X-ray security screening? - Mendes, Marcia; Schwaninger, Adrian; Michel, Stefan (Frontiers in Human Neuroscience, 2013)
This paper describes a study where a new X-ray machine for security screening featuring motion imaging (i.e. 5 views of a bag are shown as an image sequence) was evaluated and compared to single view imaging available on conventional X-ray screening systems. More specifically, it was investigated whether with this new technology X-ray screening of passenger bags could be enhanced to such an extent that laptops could be left inside passenger bags, without causing a significant impairment in threat detection performance. An X-ray image interpretation test was created in four different versions, manipulating the factors packing condition (laptop and bag separate vs. laptop in bag) and display condition (single vs. motion imaging). There was a highly significant and large main effect of packing condition. When laptops and bags were screened separately, threat item detection was substantially higher. For display condition, a medium effect was observed. Detection could be slightly enhanced through the application of motion imaging. There was no interaction between display and packing condition, implying that the high negative effect of leaving laptops in passenger bags could not be fully compensated by motion imaging. Additional analyses were carried out to examine effects depending on different threat categories (guns, improvised explosive devices, knives, others), the placement of the threat items (in bag vs. in laptop) and viewpoint (easy vs. difficult view). In summary, although motion imaging provides an enhancement, it is not strong enough to allow leaving laptops in bags for security screening.